ANALISIS FAKTOR YANG MEMPENGARUHI PERUSAHAAN MENGAMBIL KEPUTUSAN LINDUNG NILAI (HEDGING) DENGAN INSTRUMEN DERIVATIF - Mayang Puspita Zahra; Achmad Tjahjono (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to analyze the factors that influence the decision making of hedging with derivative instruments in manufacturing companies with Miscellaneous Industry sectors on the Indonesia Stock Exchange 2015-2018. The factors include: Leverage, Liquidity, Growth Opportunities, Managerial Ownership, Dividend Policy The analytical method used in this study is the logistic regression method. The population of this research is the Miscellaneous Industry Sector Company. By using purposive sampling technique, there are 22 companies with 4 years of observation from 2015-2018, obtained 88 research samples.Based on the results of the study of the five independent variables on the dependent variable, the variable liquidity, growth opportunity, managerial ownership showed the results had a significant effect on hedging decisions with derivative instruments. Other variables such as leverage and dividend policy have no significant effect on hedging decisions with derivative instruments.